DEVELOP LANGUAGE SKILL USING CERMAT CARD FOR CHILDREN GROUP A - Risma Nor Annisa; Asniwati Asniwati (Pendidikan Guru Pendidikan Anak Usia Dini (PG PAUD) Universitas Lambung Mangkurat, 2021)
The research interest in RA children can bring up new ideas that can improve children's ability to express sentences and enrich vocabulary that becomes a reference in speaking on language skill. The purpose of this study was to describe teacher activities, children’s activities and the result of developing language skill in repeating simple sentences and enriching vocabulary. This study uses a qualitative approach with the type of classroom action research carried out in three meetings. The research subjects were ten children, there are five boys and five girls. The result showed that the teacher activities were carried out very well. Children's activities increased with the very active category and the result of the development of children's language skill obtained the Very Good Developing category (BSB). It is hoped that the result of this study can be used as a reference to develop children's abilities in aspect of language development.Keywords: Language, Repeating Simple Sentences and Enhancing Vocabulary, Method of Speaking, Articulation, Model and Make a Match.